Analisis tingkat penalaran siswa dalam pembelajaran fisika berbasis peer instruction guided inquiry - Abdurrahman, Dudung (Universitas Garut, 2025)
Analysis of Students’ Reasoning Levels in Physics Learning Based on Peer Instruction Guided Inquiry. This study aims to analyze the level of student reasoning in peer instruction guided inquiry (PIGI) based physics learning. This learning design is used to encourage students' active participation and develop reasoning skills through peer discussion, and guided inquiry. This research is a descriptive study with a sample of 30 high school students in Bandung. Students’ reasoning levels were assessed based on their responses to Concept Test I and Concept Test II, conducted before and after the guided inquiry sessions. The test instrument used was a ranking task exercise. Students’ answers were analyzed and categorized using a reasoning level rubric. The findings indicate that the majority of students demonstrated reasoning at Level 2 (subfunctional) and Level 3 (near-functional). At these levels, students were able to identify relevant variables influencing the given phenomena, but their explanations revealed limited conceptual understanding, leading to difficulties in applying knowledge to different contexts. A general improvement in reasoning level was observed, with most students showing progress from Concept Test I to Concept Test II. These results suggest that the PIGI approach holds potential for enhancing students’ scientific reasoning. However, complementary instructional strategies are needed to support students in analyzing and drawing conclusions from experimental data, enabling them to construct deeper conceptual understanding.